Pengaruh Gaya Hidup Dan Literasi Keuangan Terhadap Perilaku Konsumtif Mahasiswa Manajemen Angkatan 2022 Universitas Muhammadiyah Buton - Muhammad Rais; Nur Fadila (Jurnal Multidisipliner Bharasumba, 2026)
This study aims to examine the effect of lifestyle and financial literacy on the consumptive behavior of Management students from the 2022 cohort at Universitas Muhammadiyah Buton. This research employed a quantitative approach using primary data collected through questionnaires. Data were gathered through field research, literature review, and questionnaires measured using a Likert scale. The data were analyzed using multiple linear regression analysis. The findings indicate that, partially, the lifestyle variable (X1) has a positive and significant effect on consumptive behavior (Y), with a calculated t-value of 8.456, which is greater than the t-table value of 1.979, and a significance value of 0.000 (< 0.05). Meanwhile, the financial literacy variable (X2) has a negative and significant effect on consumptive behavior (Y), with a calculated t-value of -3.245, which exceeds the critical t-value in absolute terms, and a significance value of 0.002 (< 0.05). Simultaneously, lifestyle and financial literacy have a significant effect on consumptive behavior, as evidenced by the F-test result with a calculated F-value of 43.458 and a significance value of 0.000. Therefore, lifestyle and financial literacy play important roles in shaping students' consumptive behavior.